Inflammation and neuronal plasticity: a link between childhood trauma and depression pathogenesis - Cattaneo, Annamaria; Macchi, Flavia; Plazzotta, Giona; Veronica, Begni; Bocchio-Chiavetto, Luisella; Riva, Marco Andrea; Pariante, Carmine Maria (Frontiers in Cellular Neuroscience, 2015)
During the past two decades, there has been increasing interest in understanding and characterizing the role of inflammation in major depressive disorder. Several evidences linked inflammation to major depression, including the presence of elevated levels of pro-inflammatory cytokines, together with other mediators of inflammation both in the blood and in the brain of depressed patients. However, whether depression itself acts in an immunomodulatory fashion or whether other factors related to depression result in these immunological effects remains an open question. Regardless, major depression is often the result of the exposure to stressful events early in life, which may also act through the modulation of inflammatory responses. Indeed, subjects with a history of childhood trauma show high levels of pro-inflammatory cytokines and an increased risk to develop psychopathologies later in life. Moreover, depressed patients with a history of childhood trauma are also less responsive to antidepressant therapies, suggesting that increased inflammation or altered activation of the immune system may also be relevant for the response to antidepressant therapies. This review will provide an overview on the potential role of the inflammatory/immune system and stress related biomarkers to aid diagnosis, predict treatment response, enhance treatment matching, and prevent the onset or relapse of major depression. We will also discuss the role of early life adverse events in increasing the vulnerability to depression development by acting on the inflammatory and stress-related system. Finally, we will discuss the putative biological mechanisms underlying the transmission, from one generation to the next, of the stress signatures and thus, of the increased vulnerability for psychopathologies induced by childhood trauma events.